2008
DOI: 10.1074/jbc.m801826200
|View full text |Cite
|
Sign up to set email alerts
|

Decidual Cells Produce a Heparin-binding Prolactin Family Cytokine with Putative Intrauterine Regulatory Actions

Abstract: Pregnancy in mice and rats is associated with the production of a large family of hormones/cytokines related to prolactin (PRL). The hormones/cytokines are hypothesized to coordinate maternal and fetal adaptations to pregnancy. In this study, PRLlike protein-J (PLP-J, also known as PRL family 3, subfamily c, member 1 (Prl3c1)) is shown to be a product of the uterine decidua and a regulator of postimplantation intrauterine events. PLP-J-specific antibodies and a series of recombinant PLP-J proteins were generat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 66 publications
2
22
0
Order By: Relevance
“…Our recent proteomics analysis found downregulation of a decidua-enriched prolactin-like hormone, prolactin-like protein J (PLP-J), in Trp53 loxP/loxP Pgr Cre/+ deciduae (24). PLP-J was identified in rat decidua and is implicated in maintaining decidual cell survival (25)(26)(27)(28). Our in situ hybridization results show that Prl3c1, encoding PLP-J, was highly expressed in the decidua surrounding the developing embryo on day 8 in Trp53 loxP/loxP Pgr +/+ females but was markedly downregulated in Trp53 loxP/loxP Pgr Cre/+ deciduae, consistent with our previous proteomics results ( Figure 2A).…”
Section: Trp53 Loxp/loxp Pgrsupporting
confidence: 82%
“…Our recent proteomics analysis found downregulation of a decidua-enriched prolactin-like hormone, prolactin-like protein J (PLP-J), in Trp53 loxP/loxP Pgr Cre/+ deciduae (24). PLP-J was identified in rat decidua and is implicated in maintaining decidual cell survival (25)(26)(27)(28). Our in situ hybridization results show that Prl3c1, encoding PLP-J, was highly expressed in the decidua surrounding the developing embryo on day 8 in Trp53 loxP/loxP Pgr +/+ females but was markedly downregulated in Trp53 loxP/loxP Pgr Cre/+ deciduae, consistent with our previous proteomics results ( Figure 2A).…”
Section: Trp53 Loxp/loxp Pgrsupporting
confidence: 82%
“…Despite this difference, there is a clear and consistent widespread upregulation of a diverse array of these genes, pointing to a common mechanism of regulation in response to placental ischemia. Interestingly, a correlation between preeclampsia and increased prolactin expression was noted as early as the 1970s, and extensive characterization by the Soares laboratory has demonstrated differential temporal and tissue regional localization of a number of these transcripts in the placenta during pregnancy (Ain et al 2003; Alam et al 2008; Orwig and Soares 1999; Redman et al 1975; Soares et al 2007; Wang et al 2000; Wiemers et al 2003). Several recent studies have indicated a link between preeclampsia and elevated prolactin.…”
Section: Discussionmentioning
confidence: 99%
“…Guinea pig flag-tagged PRL and PRLRP1 were identified with anti-FLAG M2 antibodies (Sigma-Aldrich) and visualized by enhanced chemiluminescence according to the manufacturer's instructions (Amersham Biosciences, Piscataway, NJ). Flag-tagged rat PRL-like protein-J (PLP-J) (32) and mock-transfected HEK-293 cells were used as positive and negative controls, respectively.…”
Section: Western Blot Analysismentioning
confidence: 99%